The endogenous responses during the flowering stage of Torenia fournieri L. under LED light - Tran, Tuan Trong; Tuong Han, Doan Do; Huu Ho, Nguyen; Tan Nhut, Duong (Vietnam Journal of Biotechnology, 2020)
The quality of light has played an important role not only in the vegetative growth, but also in the reproductive stage of the plant. Normally, the endogenous transformation has hardly been observed under the general condition. This study analyzed the endogenous changes, which were particularly influenced by the spectrum of light emitting diode (LED) with induction flowering time from 30th to 40th day. In the 40th day of the flowering process, when the average number of flower buds get the highest, endogenous carbohydrate content was decreased. However, in this phase, plants need more energy; therefore, the net photosynthetic rate tends to increase in order to supply energy for flowering. Throughout 40 days of culture, the net photosynthetic rate had an increase in the concentration of CO2. In particular, it reached the peak when being induced under the light combination ratio 7:3 of red and blue light (0.222 µmol mol-1 h-1). The sugar content also followed the same trajectory; however, it dropped at the end of the period. Among all the experiments, the ratio of red and blue light 5:5 resulted in the highest content of endogenous carbohydrate source (722.30 µg g-1). Moreover, the morphological anatomy of shoot apical meristem in flowering stage was also studied. The floral transition at meristem and floral architecture is as similar as that of Arabidopsis. A typical flower of T. fournieri also consists of a sequence: sepals – petals – stamens – carpels. The SAM is organized into three different zones such as the central zone (CZ), the peripheral zone (PZ) surrounding the CZ and the rib zone (RZ) underneath the CZ.